Risk stratification based on academic research consortium high bleeding risk criteria for long-term bleeding event after everolimus-eluting stent implantation. (25th November 2020) - Miura, K; Shimada, T; Ohya, M; Murai, R; Amano, H; Kubo, S; Tada, T; Tanaka, H; Fuku, Y; Goto, T; Kadota, K
Abstract: Background: Recently, the Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria has been suggested as the standard definition of HBR. Purpose: We aimed to investigate the risk stratification based on ARC-HBR Criteria for long-term bleeding event after everolimus-eluting stent implantation Methods: The study population comprised 1193 patients treated with EES without in-hospital event between 2010 and 2011. Individual ARC-HBR criteria was retrospectively assessed. Major bleeding were defined as the occurrence of a Bleeding Academic Research Consortium type 3 or 5 bleeding event. The mean follow-up period was 2996±433 days. Results: There were 656 patients (55.0%) in HBR-groups. Cumulative incidence of major bleeding was significantly higher in HBR-group (8.1% vs 3.4% at 4 year, and 16.2% vs 5.7% at 8 year, P<0.001). Cumulative rate of major bleeding tend to be higher as the number of ARC-HBR criteria increased (≥2 Majors: 24.3%, 1 Major: 17.0%, ≥2 Minors:11.7%, and Non-HBR: 5.7%, P<0.001). Conclusion: ARC-HBR criteria successfully stratified the long-term bleeding risk after drug-eluting stent implantation in real-world practice. Funding Acknowledgement: Type of funding source: None